Bapak yang Berkelahi, Mama yang Korban: Studi Ketimpangan Gender dalam Tata Kelola Air di Pulau Semau - Adriana Nomleni; Septiani Suyono (ISJN Journal, 2021)
Water is a basic human need. In rural areas, water is used for domestic and agricultural needs. However, the availability of water in the sense of easy access to water is not always enjoyed by rural residents. Semau Island, which is classified as a small island and has limited water resources, has easy access to water developed through infrastructure development from water sources to settlements. In theory, the development of infrastructure to bring water resources closer to home can increase access of all citizens to water. In fact, the existence of water infrastructure actually causes conflicts. Conflicts that occur are claims to water sources and destruction of infrastructure. Over a period of 6 months, through a number of focused discussions in six villages administratively located on Semau Island, it was found that women who interacted more with water actually did not have room to participate in improving water governance. Women who take water from water sources on a daily basis, manage and manage household water use are more passive parties. Meanwhile, a group of men who are actually the heirs of agrarian resources on Semau Island are busy in dispute over water. The absence of women's role in water governance is the implication of gender inequality in chronic society. Without strengthening women to help determine water governance, women will continue to be victims in water disputes, the main actors being men.